Relationship between personality traits and work performance among potential paddy farmers in Malaysian granary areas - Shayid Khalim Shah, Sarita (2016)
Paddy is the third most widely planted crop in Malaysia. According to Department of Agriculture, 686,050 hectares were planted by paddy. The total population in Malaysia is reaching 32 million by 2020. However, Malaysia is facing problem in producing adequate paddy to feed the population. This study related Rogers theory, in context most of the paddy production and they formed 68% of potential paddy farmers. However, this study only focuses on human behaviour of paddy farmers to achieve a good work performance. The objective of the study is to determine the relationship of personality traits to work performance among potential paddy farmers in Malaysia. A survey using well-structured questionnaire was carried out. The respondents were chosen using cluster sampling technique. Four out of ten granaries were selected and the total respondents are 546. Descriptive analysis was used to simplify and describe the socio demographic of the respondents. Correlation and multiple regressions were used to examine the strength and relationship of the personality traits with work performance. The correlation coefficients shows that six personal traits variables positively correlated and one personal traits variables was negatively correlated with work performance at 0.05 significant level respectively. Multiple regression analysis explains 3 variables i.e. are ability to solve problem, information network and discipline have significant with work performance. These variables explain 44% variance of the work performance (adjusted R2 = 0.441; f = 62.395, p < 0.05). Therefore, extension program should focus on these three variables in other to increase work performance.